Management of the penetrating atherosclerotic ulcer in the descending thoracic aorta. (September 2021) - Meharban, Nehman; Munir, Wahaj; Idhrees, Mohammed; Bashir, Ali; Bashir, Mohamad
Penetrating atherosclerotic ulcers present with an insidious onset with a reported mortality of 9%, varying across populations. With vast arrays of risk factors and potentially ominous complications, it is vital to efficiently provide optimum strategies for management. There exists controversy in the literature regarding management, especially for Type B penetrating atherosclerotic ulcers; the decision-making framework encompasses numerous factors in considerations for medical management versus invasive intervention and choice of endovascular versus open repair in the latter. The concomitant presence of intramural haematoma adds further complexity to the already intricate decision-making for management. We performed searches through PubMed and SCOPUS analysing studies reporting outcomes for management strategies for penetrating atherosclerotic ulcers treatment, focusing on Type B, further seeking to analyse studies reporting their experiences of PAU patients with concomitant intramural haematoma. Our review highlights the ambiguity and controversy existing in the literature, comprising studies burdened by their inherent hindering limitations of their single-centre retrospective experiences. Endovascular therapy has come to the forefront of penetrating atherosclerotic ulcers management, often considered first line therapy. In the case of penetrating atherosclerotic ulcers alongside intramural haematoma, there have been reports of potential hybrid surgical approaches to management. Studies further show misdiagnosis of penetrating atherosclerotic ulcers in earlier data sets further complicates management. However, it is clear we must progress on the journey towards precision medicine, allowing delivery of optimum care to our patients.